Special issues in assessing a positive energy district as a part of sustainable development - Alyokhina, Svitlana (AiBi Revista de Investigación, Administración e Ingeniería, 2025)
The Positive Energy District (PED) concept is integral to achieving Global Sustainable Goals, representing a crucial component of comprehensive sustainability efforts. This work delves into specific issues that are infrequently addressed but hold significance to PED projects or may exhibit correlations with other performance indicators. These include discussions on "green infrastructure," "waste utilization," "energy and emission footprints on household level," "farmland usage," and the composite indicator "quality of life per greenhouse gas emission." Each topic is examined within the context of its conventional understanding, and the primary approaches for studying them are elucidated.
Keywords: positive energy districts; greenhouse gas emission; waste utilization; green infrastructure; urban farming